(untitled) (MAUSAM, 1978)
In the years of large scale failure of southwest monsoon rainfall over India during the decade 1965 to 1974, the mean meridional circulation over India during July and August is of the type occurring in association with ’break monsoon’ situations, i.e.. meridional northward motion in the upper troposphere, north of-latitude about 200 N. During such years subtropical westerlies of the upper troposphere seem to protrude more southward into the areas immediately west of India during the monsoon season; this feature persisting on many occasions, right from the preceeding winter, which may explain the preferred northward tracks of the November cyclones of the Bay of Bengal, the occurrence of low 500 mb altitudes over northwest Indian stations during winter and pre-monsoon seasons and the observed greater frequency, and duration of ’break monsoon’ spells associated with the large scale monsoon failures as earlier reported by Joseph (1975, 1976).